2015
DOI: 10.1088/0964-1726/25/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Static and fatigue tensile properties of cross-ply laminates containing vascules for self-healing applications

Abstract: The effect of including hollow channels (vascules) within cross-ply laminates on static tensile properties and fatigue performance is investigated. No change in mechanical properties or damage formation is observed when a single vascule is included in the 0/90 interface, representing 0.5% of the cross sectional area within the specimen. During tensile loading, matrix cracks develop in the 90°layers leading to a reduction of stiffness and strength (defined as the loss of linearity) and a healing agent is inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…3 The crack growth rates in notched and un-notched samples were compared to find the strain energy (tearing energy) under repeated vibrational fatigue conditions. Self-healing effect on the fatigue crack propagation and the corresponding arrest mechanisms were studied using healing agent microcapsules in epoxy matrix composite 33 , carbon-fiber composite, 34 vascules in cross-ply laminates, 35 manual infiltration of fast-curing epoxy to tapered double cantilever beam (TDCB), 36 as well as hydrogel for fatigue resistance. 37 As the tensile fatigue at the crack tip increases, cracks start growing at the pre-notch locations.…”
mentioning
confidence: 99%
“…3 The crack growth rates in notched and un-notched samples were compared to find the strain energy (tearing energy) under repeated vibrational fatigue conditions. Self-healing effect on the fatigue crack propagation and the corresponding arrest mechanisms were studied using healing agent microcapsules in epoxy matrix composite 33 , carbon-fiber composite, 34 vascules in cross-ply laminates, 35 manual infiltration of fast-curing epoxy to tapered double cantilever beam (TDCB), 36 as well as hydrogel for fatigue resistance. 37 As the tensile fatigue at the crack tip increases, cracks start growing at the pre-notch locations.…”
mentioning
confidence: 99%
“…A very few studies have addressed the performance of aged (healable) composites or even their fatigue response. In the few studies that have led such investigations, healing performance has been observed to significantly deteriorate with time . More of these investigations are required, as is analysis of the root cause of the instability: only by investigating this phenomenon can effective solutions be proposed.…”
Section: Resultsmentioning
confidence: 99%
“…The self‐healing performance of cross‐ply laminates after static and fatigue loading was investigated by Luterbacher et al In this study, a 1D vascular network was created via polytetrafluoroethylene (PTFE)‐coated nickel chromium wires (0.56 mm diameter). The wires were placed at discrete intervals during the lay‐up and removed after cure.…”
Section: Self‐healing Fiber‐reinforced Polymer Composites: the State mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, fatigue resistance of self-healing polymers and polymer composites has not been extensively studied. Moreover, healing speed is not the main concern of these available works [35][36][37][38][39][40][41][42][43]. In this context, the present investigation might add to the researches in this area.…”
mentioning
confidence: 90%